Исследование методов декомпозиции моделей системы функционирования книжно-журнальных изданий с измененяемым информационным наполнением - Дурняк, Б.; Петриашвили, Г. (Моделювання та інформаційні технології, 2010)
In the article solved the problem of decomposition of the synthesized model of
the functioning the book and magazine editions and introduced the notion of pseudoorthogonality
transformation of synthesis and transformation of decomposition.